Short Communication: Plant species richness and diversity in Karangsambung-Karangbolong National Geopark, Indonesia - angga yudaputra; Puguh Rahardjo (Society for Indonesian Biodiversity, 2020)
Abstract. Yudaputra A, Rahardjo P. 2020. Short Communication: Plant species richness and diversity in Karangsambung-Karangbolong National Geopark, Indonesia. Biodiversitas 21: 1735-1742. The information on plant species richness and diversity in Karangsambung-Karangbolong National Geopark, Central Java is very limited. This study aimed: (1) to investigate plant species richness and abundance as well as floristic composition in Karangsambung-Karangbolong National Geopark; (2) to reveal the potential uses of plant species recorded in the area. Square sampling plots were applied for nine sampling locations. Square plot of 10 x 10 m was applied to record tree, while nested plots of 5 x 5 m and 2 x 2 m were applied to record sapling and understorey plants including shrubs and herbs, respectively. The highest plant species richness was found in the location with higher elevation and mountainous topography. The species abundance reaches its maximum values at low to moderate elevation. Shannon Diversity Index (H) showed that tree and sapling have moderate diversity, whereas understorey plant has high diversity. Melastoma malabathricum, Clidemia hirta, Zingiber zerumbet, and Ageratum conyzoides are the most abundant plants in this Geopark. Most of plants recorded have potential benefit as medicinal uses.